2020
DOI: 10.1590/0004-282x20190186
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic drugs alter beta coherence during motor imagery and motor execution in healthy adults

Abstract: Background: Motor Imagery (MI) represents the cognitive component of the movement and recruits dopaminergic systems. Objective: To investigate the role of dopaminergic system through the action of methylphenidate and risperidone over beta coherence during execution, action observation and motor imagery. Methods: Electroencephalography (EEG) data were recorded before and after the substance intake. For statistical analysis, a three-way ANOVA was used to identify changes in beta coherence induced by the group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A previous study demonstrated that the activation of neurocognition was triggered by a process of MI and AO training and was associated with brain plasticity-based regulation of neural pathways. 46 Action observation has also been found to be crucial to the process of motor cognition and motor learning, because of the congruent relationship between an observed action and a previous action experience. This indicates that AO is also involved in motor perception, memory, and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the activation of neurocognition was triggered by a process of MI and AO training and was associated with brain plasticity-based regulation of neural pathways. 46 Action observation has also been found to be crucial to the process of motor cognition and motor learning, because of the congruent relationship between an observed action and a previous action experience. This indicates that AO is also involved in motor perception, memory, and decision making.…”
Section: Discussionmentioning
confidence: 99%